(untitled) (Ustozlar uchun, 2025)
This article examines the impact of reading on writing development in EFL learners, emphasizing the close relationship between receptive and productive language skills. Reading provides learners with exposure to vocabulary, grammatical structures, text organization, and discourse patterns, all of which play a crucial role in shaping effective writing. The study discusses how different types of reading activities, including extensive and intensive reading, contribute to the development of writing accuracy, coherence, and stylistic awareness. By reviewing theoretical perspectives and practical classroom examples, the article highlights the importance of integrating reading into writing instruction in EFL contexts.